2017
DOI: 10.7717/peerj.3474
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive singular spectrum analysis method for extracting brain rhythms of electroencephalography

Abstract: Artifacts removal and rhythms extraction from electroencephalography (EEG) signals are important for portable and wearable EEG recording devices. Incorporating a novel grouping rule, we proposed an adaptive singular spectrum analysis (SSA) method for artifacts removal and rhythms extraction. Based on the EEG signal amplitude, the grouping rule determines adaptively the first one or two SSA reconstructed components as artifacts and removes them. The remaining reconstructed components are then grouped based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…The variation in the length of EEG waves is difficult to study because of disturbances and stochastic noise. Although there are methods for removing artifacts (Teixeira et al 2006, Daly et al 2013, Hu et al 2017, these procedures change the shape of the waves, and this affects the measurements. Therefore, only sequences of waves with a minimal amount of disturbances and noise should be included in a study of the wavelength variation.…”
Section: Methodsmentioning
confidence: 99%
“…The variation in the length of EEG waves is difficult to study because of disturbances and stochastic noise. Although there are methods for removing artifacts (Teixeira et al 2006, Daly et al 2013, Hu et al 2017, these procedures change the shape of the waves, and this affects the measurements. Therefore, only sequences of waves with a minimal amount of disturbances and noise should be included in a study of the wavelength variation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its great success in terms of handling climatic, meteorological, and geophysical data [29], the SSA-based algorithm has been used to analyse EEG signals. Maddirala and Shaik made use of the method based on SSA to eliminate EOG [30] and motion artifacts [31] from EEG in the case of only one channel; Teixeira et al presented an approach to extract high-amplitude artifacts [32]; Hu et al suggested utilizing the method derived from SSA to extract desired brain rhythms [33]. On the basis of these studies, we know that SSA can succeed in separating EEG composed of different sources, which are mixed with each other in the time-frequency domain.…”
Section: Introductionmentioning
confidence: 99%
“…Then a new grouping rule based on the local mobility of the eigenvectors was proposed to remove the motion artifact, which performed better than the traditional method [ 19 ]. Based on the similarity of the eigenvalues and the peak frequency of RC, Hai et al proposed another efficient grouping rule enabling SSA to be adaptive to EEG signals containing different levels of artifacts and rhythms [ 25 ]. However, for the issue of embedding dimension selection, to the best of our knowledge, there is no explicit rule for embedding dimension selection.…”
Section: Introductionmentioning
confidence: 99%